Awareness, Benefits, and Services: Lecturers’ Perceived Towards The Application of ISO 9001: 2008 at University - Ahmad Syukri; Nisaul Fadillah (IJER (Indonesian Journal of Educational Research), 2017)
Abstract: The State Islamic Institute Sulthan Thaha Saifuddin (IAIN STS) Jambi has been applying ISO 9001; 2008 since February 2013. One of previous research findings was the resistance regarding the ISO standards and the certification process. This study was to examine the problem through conducting lecturers’ perception towards ISO 9001; 2008 at IAIN STS Jambi in terms of their awareness, benefits and services. Respondents were lecturers of IAIN STS Jambi as many as 122 people from 4 faculties. The research employed a quantitative survey method that uses a likert-scale questionnaire and analysed with descriptive statistic. The findings show that lecturers’ perception on the application of TQM ISO 9001: 2008 in IAIN STS Jambi included in the group of moderate to high. The mean empirical data (x = 47,30) was higher than the average hypothetical (μ = 42). This indicates that the perception of lecturers on the application of ISO in IAIN STS Jambi is high (positive). Empirical standard deviation (s = 9,910) was higher than the hypothetical standard deviation (σ = 9:33). This shows that the perception of lecturers on the application of ISO 9001: 2008 at IAIN STS Jambi has a high variation. Meanwhile, gender variable has a significant relationship between the perception of ISO 9001: 2008 on improving the quality of teaching. Employment status (fulltime civil employer or non-full-time civil employer) have a significant relationship between the perception of ISO 9001; 2008 for quality of services and quality of coordination.